2010
DOI: 10.1007/bf03337729
|View full text |Cite
|
Sign up to set email alerts
|

Lower extremity strength and power asymmetry assessment in healthy and mobility-limited populations: reliability and association with physical functioning

Abstract: Background and aims-This study assessed the reliability of evaluating asymmetrical strength and power deficits in the lower limbs of healthy middle-aged, healthy older and mobility-limited elders. We also explored the relationship between limb asymmetry and physical functioning.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
57
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(62 citation statements)
references
References 25 publications
4
57
1
Order By: Relevance
“…These data indicate that the independent power of limbs is more closely related to function than the symmetry of power between limbs, which is in agreement with previous work by Carabello et al (2010). The Boston RISE study found that while leg strength asymmetry was a significant predictor of self-reported lower-extremity function in older adults, it had the lowest association of the neuromuscular predictor variables, particularly in comparison to leg strength (Bean, Latham et al 2013).…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…These data indicate that the independent power of limbs is more closely related to function than the symmetry of power between limbs, which is in agreement with previous work by Carabello et al (2010). The Boston RISE study found that while leg strength asymmetry was a significant predictor of self-reported lower-extremity function in older adults, it had the lowest association of the neuromuscular predictor variables, particularly in comparison to leg strength (Bean, Latham et al 2013).…”
Section: Discussionsupporting
confidence: 91%
“…It should be noted that previous investigations of strength and power asymmetry in older adults have used a range of testing modalities including pneumatic resistance, the Nottingham Power Rig, and isokinetic dynamometry, and, some studies measured knee extensor asymmetry whereas others measured whole-leg asymmetry (Skelton, Kennedy et al 2002, Portegijs, Sipila et al 2005, Perry, Carville et al 2007, Carabello, Reid et al 2010, LaRoche, Cook et al 2012, Bean, Latham et al 2013, Straight, Brady et al 2016, Ward, Beauchamp et al 2016). These studies are therefore not directly comparable because of the task-specificity of asymmetry and the use of compensatory mechanisms that may mask single-joint strength and power asymmetries during whole-leg exercises (Bond, Cook et al 2017).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Similarly, asymmetry of leg power was measured as the ratio of the peak leg press power in a similar fashion (17).…”
Section: Asymmetry Of Leg Strength and Leg Powermentioning
confidence: 99%